(untitled) (Bangladesh Journal of Medical Science, 2026)
Background The successful insertion of dental implants is highly proportional to the condition and quantity of the alveolar bone at the edentulous area. This pilot study aimed at evaluating clinically & radiographically the efficacy of preservation of alveolar ridge by making use of platelet- rich fibrin (PRF) & β – tricalcium phosphate TCP)+rh- bone morphogenic protein (BMP)-2 followed by delayed implant placement. Materials & Methods Post-extraction sockets were augmented using a combination of autologous PRF and alloplastic bone graft (β-TCP) mixed with growth factor rh-BMP 2. At three months, the clinical and radiographic study was carried out, and implants were placed using two staged protocols. Outcome clinical parameters involving mean modified plaque index (MPI), modified bleeding index (MBI), clinical implant mobility score (CIMS), full mouth plaque index (FMPI), full mouth papillary bleeding index (FMPBI), probing measurements such as probing pocket depth (PPD), gingival recession (GR), and width of keratinized gingiva (WKG) around implants were evaluated. Results A total of 12 sockets in 9 patients were treated using the ridge preservation technique. At three months after extraction & ridge preservation, baseline evaluation revealed minimal buccolingual dimensional changes (7.0 mm ± 1.21 mm). Following implant placement, radiographic evaluation at 3 months showed minimum vertical & horizontal loss in bone (mesial: 0.33 ± 0.33, distal: 0.25 ± 0.33). Use of rhBMP-2+ β -TCP+rh-BMP-2 reduces the dimensional changes owing to 100% survival of the implants. Conclusion Atraumatic extraction employing ridge preservation using PRF & β -TCP+rh-BMP-2 followed by delayed implant placement minimizes dimensional changes and helps in the improved success rate of the implant BJMS, Vol. 25 No. 01 January’26 Page : 334-342